Preparation of Pillar[5]arene‐Based [2]Rotaxanes from Acyl Chlorides and Amines1. Issue 3 (4th December 2014) - Milev, Radian; Lopez‐Pacheco, Alberto; Nierengarten, Iwona; Trinh, Thi Minh Nguyet; Holler, Michel; Deschenaux, Robert; Nierengarten, Jean‐François
Abstract: Pillar[5]arene‐based [2]rotaxanes have been prepared from the reactions of diacyl chloride reagents with various amine stoppers. The yields of the [2]rotaxanes are sensitive to the reaction conditions (solvent and stoichiometry) as well as to structural and electronic factors. In particular, the nature of the starting amine reagent has a dramatic influence on the yields of [2]rotaxanes; thus, the reaction outcome is not simply related to the binding constant of the diacyl chloride reagent with the pillar[5]arene. Indeed, the differences in the yields must be related to the different affinities for the various monoacylated intermediates. The yields of the [2]rotaxanes are also influenced by several structural factors such as the chain length of the diacyl chloride reagent and the size of the peripheral substituents of the pillar[5]arene building block. Finally, the preparation of [2]rotaxanes from alkyldiamine reagents and acyl chloride stoppers has also been investigated. Abstract : The yields of pillar[5]arene‐based [2]rotaxanes from the reactions of diacyl chloride reagents with various amine stoppers are sensitive to the reaction conditions (solvent and stoichiometry) as well as to structural and electronic factors.